2022
DOI: 10.1001/jamanetworkopen.2022.27667
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Outcomes From 1-Year Surveillance After Detection of Early Gastric Cancer Among Patients at High Risk in Japan

Abstract: IMPORTANCE Single endoscopic examination often misses early gastric cancer (GC), even when both high-definition white light imaging and narrow-band imaging are used. It is unknown whether new GC can be detected approximately 1 year after intensive index endoscopic examination. OBJECTIVE To examine whether new GC can be detected approximately 1 year after intensive index endoscopic examination using both white light and narrow-band imaging. DESIGN, SETTING, AND PARTICIPANTSThis case-control study was a preplann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Consistently, we excluded gastric cancers diagnosed within 1 year of the index date from the analysis to account for the likelihood of synchronous lesions. We agree that a considerable proportion of gastric neoplasms may be missed during endoscopic examination 3–5 . Indeed, out of 22,788 patients, 3912 developed gastric neoplasms within 1 year of the index date and were therefore excluded.…”
mentioning
confidence: 75%
“…Consistently, we excluded gastric cancers diagnosed within 1 year of the index date from the analysis to account for the likelihood of synchronous lesions. We agree that a considerable proportion of gastric neoplasms may be missed during endoscopic examination 3–5 . Indeed, out of 22,788 patients, 3912 developed gastric neoplasms within 1 year of the index date and were therefore excluded.…”
mentioning
confidence: 75%
“…NBI did have a better positive predictive value in diagnosing cancer. Furthermore, a one‐year follow‐up of this high‐risk cohort demonstrated that intensive index endoscopy, with both white light and second‐generation NBI, was not associated with a reduction in the rates of detections of new GC 70 . Hence the limitations of both modalities highlight an unmet need in detecting early cancers.…”
Section: Image‐enhanced Endoscopymentioning
confidence: 89%
“…Furthermore, a one‐year follow‐up of this high‐risk cohort demonstrated that intensive index endoscopy, with both white light and second‐generation NBI, was not associated with a reduction in the rates of detections of new GC. 70 Hence the limitations of both modalities highlight an unmet need in detecting early cancers. The application of IEE also involves a learning curve though this may be negotiated with training.…”
Section: Image‐enhanced Endoscopymentioning
confidence: 99%
“…LM-NBI began on the rst day of March 2019, and 1 month was set as the incubation period. The clinical medical records of the patients were reviewed, and patients who underwent conventional endoscopy (CE) within a year (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) Patients who visited Nagashima Clinic for check-ups or routine follow-ups for chronic gastritis were included. Patient demographics and clinical characteristics were obtained from medical records.…”
Section: Methodsmentioning
confidence: 99%
“…I empirically set the surveillance period to 1 year because annual and biennial screening is prevalent in Asia 2 . Neoplasias were constantly identi ed during annual observation, and a recent report emphasized the e cacy of 1-year surveillance using WLI and NBI 14 . This annual interval seems appropriate for screening patients with chronic gastritis.…”
Section: Declarations Data Availabilitymentioning
confidence: 99%